2020
DOI: 10.1186/s12935-020-01287-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circular RNA circ-CSPP1 regulates CCNE2 to facilitate hepatocellular carcinoma cell growth via sponging miR-577

Abstract: Objective: Circ-centro-some/spindle pole-associated protein (CSPP1) has been confirmed to be characterized in diverse human malignancies and its ectopic expression may regulate tumor progression and development. However, in hepatocellular carcinoma (HCC), its biological role, clinical significance and molecular mechanism are still unclear. Methods: Circ-CSPP1 expression and its prognostic values in HCC tissues were detected by qRT-PCR or in situ hybridization (ISH), and enriched by using Rnase R. The functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…Several recent studies have reported the oncogenic role of circ-CSPP1 in ovarian cancer, cervical cancer, glioma, and hepatocellular carcinoma [ 21 , 22 , 23 , 24 ]. Here, our work showed a remarkable overexpression of circ-CSPP1 in CRC, in agreement with the recent work [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have reported the oncogenic role of circ-CSPP1 in ovarian cancer, cervical cancer, glioma, and hepatocellular carcinoma [ 21 , 22 , 23 , 24 ]. Here, our work showed a remarkable overexpression of circ-CSPP1 in CRC, in agreement with the recent work [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work reported the promoting effect of circ-CSPP1 on the stemness of CRC cells through the miR-193a-5p/COL1A1 axis [ 10 ]. Recent studies also identified the oncogenic role of circ-CSPP1 in human carcinogenesis by regulating the miR-361-5p/ITGB1 or miR-577/CCNE2 axis [ 22 , 24 ]. These findings suggest that there may be many other miRNA/mRNA axes that remain to be identified in the regulation of circ-CSPP1.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, circ-CSPP1 contributes to HCC growth and invasion through sponging miR-577. 21 circ_0072995 was found to be the ceRNA for miR-147a and miR-30c. 12,13 In HCC, we did not observe it.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies agree that the increased expression of these 5 genes is associated with a poor prognosis and more advanced tumor stages in HCC patients [ 13 , 26 30 ]. Moreover, research showed that E2F1 regulates DNAJA1 to promote cell proliferation and metastasis by stabilizing CDC45 in colorectal cancer cell lines [ 21 ] and that silencing CCNE2 or CENPM could inhibit HCC cell growth [ 30 , 31 ]. Therefore, CDC45 may have a synergistic relationship with NUDT1 , E2F1 , CCNE2 , MCM5 , and CENPM that promotes the oncogenesis and progression of HCC.…”
Section: Discussionmentioning
confidence: 99%